Automobile sector in India at the current juncture: Crisis and prospects - Praveen K. Jha; Preksha Mishra; Kamya Singh (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
As the COVID-19 pandemic wreaked havoc along Global Value Systems (GVSs) and India's domestic economic crisis deepened, the already struggling Indian Automotive sector incurred huge losses owing to both demand and supply side factors. In fact, the sector has been under significant strain over the past decade, which only intensified by 2018-19. Since the pandemic, several policies have been initiated to 'revive' the industry and to achieve the sector's tremendous export potential; particular emphasis has been placed on technological advancement. The sector has been increasingly integrated into GVSs since the 1990s such that a large share of domestic production in the automobile and auto components industry is exported. However, India's share in global exports in the auto sector has remained modest and the sector has flourished predominantly in the mass production of low-value and low-tech commodities. This paper seeks to assess the current state of the automotive industry in India against the background of the pandemic using both primary and secondary sources. For this purpose, two surveys were conducted in India in 2022 and early 2023; the first was undertaken in select automobile clusters and auto components manufacturers while the second, focused on multiple stakeholder categories across the industry - companies, policymakers and Trade Unions. The impact of the crisis, the subsequent 'recovery' and the future prospects of the sector have been examined through the lens of the industry performance and that of the world of work.
Keywords: P1; J21; J65; O14; I; 330; Global value systems/chains; COVID-19; labour; Relative Surplus Population; Neoliberalism; exports; technological advancement; Manufacturing; Automobiles; auto components; Capitalism